2007
DOI: 10.1523/jneurosci.4739-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Microcircuitry for Two Types of Achromatic Ganglion Cell in Primate Fovea

Abstract: Synaptic circuits in primate fovea have been quantified for midget/parvocellular ganglion cells. Here, based on partial reconstructions from serial electron micrographs, we quantify synaptic circuits for two other types of ganglion cell: the familiar parasol/magnocellular cell and a smaller type, termed "garland." The excitatory circuits both derive from two types of OFF diffuse cone bipolar cell, DB3 and DB2, which collected unselectively from at least 6 Ϯ 1 cones, including the S type. Cone contacts to DB3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 69 publications
3
66
1
Order By: Relevance
“…Together with our findings indicating that WNT7B was localized to retinal ganglion cells and that its expression was significantly upregulated in experimental myopic eyes, these data support the hypothesis that WNT7B and GJD2 co-operatively regulate the normal growth of the eye through interactions between the alpha-ganglion cells and AII amacrine cells. Interestingly, alpha-ganglion cells are predominantly observed in the peripheral retina and have large dendritic regions to receive inputs from amacrine cells 47,[53][54][55][56][57] . The hypothesis that alpha- ganglion cells and AII amacrine cells are implicated in emmetropization is consistent with the peripheral defocus theory, a theory of myopia development that has been supported by clinical evidence [58][59][60][61] .…”
Section: Discussionmentioning
confidence: 99%
“…Together with our findings indicating that WNT7B was localized to retinal ganglion cells and that its expression was significantly upregulated in experimental myopic eyes, these data support the hypothesis that WNT7B and GJD2 co-operatively regulate the normal growth of the eye through interactions between the alpha-ganglion cells and AII amacrine cells. Interestingly, alpha-ganglion cells are predominantly observed in the peripheral retina and have large dendritic regions to receive inputs from amacrine cells 47,[53][54][55][56][57] . The hypothesis that alpha- ganglion cells and AII amacrine cells are implicated in emmetropization is consistent with the peripheral defocus theory, a theory of myopia development that has been supported by clinical evidence [58][59][60][61] .…”
Section: Discussionmentioning
confidence: 99%
“…Another ganglion cell type in macaque retina, the parasol ganglion cells, displays much more convergence compared to midget ganglion cells (Jacoby et al, 2000). Serial section electron micrographic reconstructions of the synaptic connectivity of a foveal parasol retinal ganglion cell has revealed that each cell pools input from ~ 50 cones via ~ 120 bipolar cells (Calkins and Sterling, 2007). This enables the parasol cells to encode for luminance.…”
Section: Synapse Structure and Connectivity Of Retinal Neuronsmentioning
confidence: 99%
“…Previous TEM montaging efforts produced only arrays of single images for humans to track as stacks of photographs or low resolution digital files. For neuroscience, this meant that legacy ultrastructural anatomy, which (albeit heroic in scope) actually delivered only a broad-brush concepts and only fragments of retinal networks at best (Calkins and Sterling, 1996; 2007; Calkins et al, 1998; Klug et al, 2003; Kolb and Famiglietti, 1974b; Kolb and Nelson, 1993; Stevens et al, 1980; Strettoi et al, 1992). That said, these studies discovered the baseline network for understanding signal flow in the retina.…”
Section: Connectomicsmentioning
confidence: 99%